An Investigation into Intercultural Communication Competence ofFreshman Students in Adama Science and Technology University - Dr. Mekuria Abera Mr. Tilahun Deneke (ASTU, 2018)
Intercultural communication competence is the ability to communicate effectively inmulticultural contexts. It comprises three aspects: knowledge, attitude and skills. Thisstudy aimed at investigating the intercultural communication competence of 2016/ 2009entry freshman students. The study employed a quantitative research design in whichdescriptive survey method was principally utilized. A questionnaire adapted fromIntercultural Sensitivity Scale and Assessment of Intercultural Communication was usedas a sole data gathering tool. The questionnaire was administered to 308 students whowere selected through systematic random sampling. The sample size was calculated with95% confidence level. The data collected through the questionnaire was analyzed withSPSS version 21. The results of the study revealed that the freshman students had highintercultural sensitivity. It also revealed that the students had positive attitude towardstudents who share different cultural background. Paradoxically, the results revealedthat the freshman students exhibit average intercultural knowledge. The study, therefore,recommended that multicultural events that aim at exhibiting the artifacts, values andbeliefs of the different cultural groups in the country should be organized at campuslevel. Besides it recommended that language course designers should incorporate lessonsthat raise the awareness of students about the diversity of the cultures in the country.